The effect of BMP-2 on the osteoconductive properties of beta-tricalcium phosphate in rat calvaria defects - Luvizuto, Eloa R. [UNESP]; Tangl, Stefan; Zanoni, Gerald; Okamoto, Tetuo [UNESP]; Sonoda, Celso Koogi [UNESP]; Gruber, Reinhard; Okamoto, Roberta [UNESP] (Elsevier B.V., 2011)
Bone formation in critical-sized calvaria defects is strongly dependent on the osteoconductive properties of grafts. It remains a matter of controversy whether biomaterials can replace autografts and whether the supplementation of biomaterials with Bone Morphogenetic Proteins (BMPs) is necessary to enhance bone formation. We examined rat calvaria critical-sized defects (5-mm-diameter) treated with beta-tricalcium phosphate (TCP; Cerasorb (R) M), polylactic and polyglycolic acid gel (PLA/PGA; Fisiograft (R)) and calcium phosphate cement (CPC; Norian (R) CRS (R)), either alone or in the presence of 5 mu g of BMP-2 after 45 days. Autografts and untreated defects served as controls. Bone formation was evaluated based on mu CT analysis, histomorphometric analysis and fluorescence analysis. We report that TCP supported bone formation more efficiently than did autografts. Bone formation in the presence of TCP alone reached a maximal level, as BMP-2 supplementation failed to enhance bone formation. By contrast, no significant difference in bone formation was observed when PLA/PGA and CPC were compared to autografts. Moreover, the presence of BMP-2 did not substantially change the osteoconductive properties of PLA/PGA or CPC. We conclude that the osteoconductive properties of TCP are superior to those of autografts and that TCP does not require BMP-2 supplementation. Our findings also show that the decreased osteoconductive properties of PLA/PGA and CPC cannot be overcome by BMP-2 supplementation in rat calvaria defects. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Animal model; Bone regeneration; BMP (bone morphogenetic protein); Calcium phosphate cement; Polylactic acid; Bone tissue engineering